دراسة التقليل من التبخر في سد 16 تشرين بطريقة الفقاعات المائية - عز الدين حسن; ديانا يوسف (Tishreen University, 2019)
It is known that water covers more than three-quarters of the globe, but nevertheless, the good for use is few with increasing need for water. Most Arab states will suffer - in the future - from a severe water crisis, and evaporation is one of the real problems that drain water in hot areas, especially in Arab countries located in the arid and semi-arid regions. Direct and indirect methods have been used to try to estimate the amount of water lost in this activity. Evaporation is known as the maximum amount of vapor that can be released from a certain area of ​​the earth to the atmosphere under the influence of the specific weather factors of that region. Evaporation in natural conditions takes place from the water, Soil, and vegetation. Each evaporation surface has several characteristics that affect the evaporation process. For example, "evaporation from the surface of water is related to the prevailing weather conditions in the region such as air humidity, temperature, solar brightness, wind speed, surface area and water depth. Research has been done about different methods have been explored to reduce this type of evaporation from water surfaces to conserve water that is stored in open reservoirs to alleviate the water crisis. Therefore, the objective of our study was to address the problem of evaporation in the dam lakes and to study the methods used to reduce water losses and compare them, and then choose the optimal method in the general conditions in general and in the conditions of Lattakia area, especially in 16 Tishreen dam. After the study of this research shows that among the methods that can be applied to reduce evaporation as a new water source, the most environmentally friendly because it does not affect the composition of water and suitability for different uses is the method of air bubbles or water bubbles. Experimented from the previous reference studies described later, "this method will be a very effective technique in reducing evaporation from deep water reservoirs (especially large dam lakes). This method is based on the thermal mixing of water by compressed air. After the experiments, the results were excellent, reducing the evaporation and thus the annual water loss by 7.6%. من المعروف أن المياه تغطي أكثر من ثلاثة أرباع الكرة الأرضية لكن بالرغم من كل ذلك فإن الصالح منها للاستخدام يبقى قليلاً مع تزايد الحاجة إلى الماء. إن معظم الدول العربية ستعاني - مستقبلاً - من أزمة حادة في المياه, والتبخر هو أحد المشكلات الحقيقية التي  تستنزف المياه في المناطق الحارة  و خصوصاً في  البلاد العربية الواقعة في المنطقة الجافة وشبه الجافة. استُخدِمت طرائق مباشرة وغير مباشرة لمحاولة تقدير كميات المياه المفقودة بهذه الفعالية, إذ يُعرَّف التبخر بأنه أقصى كمية من البخار يمكن أن تنطلق من مساحة معينة من الأرض إلى الجو تحت تأثير العوامل الجوية الخاصة بتلك المنطقة تحديداً, ويحصل التبخر في الظروف الطبيعية من سطوح المياه, والثلج, والتربة, ومن النباتات ويتميز كل سطح تبخر بعدة خصائص تؤثر على عملية التبخر, فمثلا" يتعلق التبخر من سطح المياه بظروف الطقس السائدة في المنطقة كنقص رطوبة الهواء, درجة الحرارة, السطوع الشمسي, سرعة الرياح, مساحة السطح وعمق المياه. وقد تم البحث عن طرائق مختلفة للتقليل من هذا النوع من التبخر من السطوح المائية للحفاظ على المياه التي يتم تخزينها في الخزانات المكشوفة للتخفيف من أزمة المياه. لذلك كان الهدف من هذه الدراسة معالجة مشكلة التبخر في بحيرات السدود ودراسة الطرائق المتبعة للتقليل من الفاقد المائي والمقارنة بينها ثم اختيار الطريقة الأمثل في الظروف العامة بشكل عام وفي ظروف منطقة اللاذقية سد 16 تشرين بشكل خاص باعتباره السد الرئيسي بالمحافظة بأكبر حجم تخزين 210 مليون م3. وبعد الدراسة التي تمت لهذا البحث تبين أنه من بين الطرائق التي يمكن تطبيقها لتقليل التبخر كمصدر مائي جديد فإن أكثرها صديقة للبيئة لعدم تأثيرها على تركيبة المياه وصلاحيتها من أجل استخدامات مختلفة هي طريقة الفقاعات الهوائية أو الفقاعات المائية. وبالتجربة ومن توصيف الدراسات المرجعية السابقة المذكورة لاحقا" لهذه الطريقة فإنها ستكون تقنية فعالة جداً في تقليل التبخر من خزانات المياه العميقة (خاصة بحيرات السدود الكبيرة) وتعتمد هذه الطريقة على الخلط الحراري للماء عن طريق الهواء المضغوط. بعد القيام بالتجارب كانت النتائج ممتازة حيث قللت من التبخر وبالتالي من الفاقد المائي السنوي بنسبة %7.6.